Med tanke på läsarna. Resebloggandets narrativa och sociala balansgång - Jansson, Hanna (Tidsskrift for kulturforskning, 2019)
This article discusses narrative and social challenges following development in communication technology. The paper aims to show how Swedish cruising sailors adapt the style and content of their online travel writing, with the interest of different audience groups in mind. How do they manage the sometimes conflicting interests of different audience groups? What is considered un-tellable, and why? The analysis is based on interviews with Swedish cruising sailors and on analysis of primarily four online cruising travelogues. The article combines folkloristic and socio-linguistic perspectives on communicative competence and on immediate or ongoing storytelling, to describe a narrative awareness of the cruisers. As I show, concern for the readers make online travel writing whilst travelling a work-like task. The cruisers develop strategies to write entertaining and exciting stories without worrying family members, and must try to instruct fellow cruisers without boring the non-sailors in the audience. Lastly, the article advocates a combination of online and offline qualitative fieldwork to enable an understanding of online and ongoing storytelling practices, and the social and narrative strategies of people active in social media.